Implementasi Metode Manajemen Stress Sebagai Sarana Edukasi Kesehatan Mental Wanita di Dharma Wanita Badan Pemeriksaan Keuangan Perwakilan Provinsi Maluku - Dewi Shinta Wulandari Lubis; Soraya Grabiella Dinamika (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
Mental health is not something that is not considered important nowadays, especially mental health in women, in fact, it is found that 47 percent of women are at a higher risk of experiencing mental health disorders than men. The high number of stresses in women can be triggered by various factors, such as family and the surrounding environment. For this reason, women, especially those who are married and working, are expected to care more about their mental health and be able to manage stress by recognizing symptoms of mental health disorders, their triggers, and how to manage stress. In this community service, community service will be carried out in the form of increasing understanding of mental health in women and stress management. This activity was carried out using the method of delivering material or workshops and continued with the practice of mindfulness (meditation) accompanied by counselors who were attended by 30 members of the Dharma Wanita Audit Board of the Republic of Indonesia (BPK) Representatives of Maluku Province. Participants feel more educated with the material that has been delivered as well as mindfulness practices that can be applied every day.